2003
DOI: 10.1136/thorax.58.10.890
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of DQB1 allele frequencies in pulmonary tuberculosis: preliminary report

Abstract: Background: The human leucocyte antigen (HLA) system plays an important role in the modulation of the immune response. An association between HLA and pulmonary tuberculosis (TB) has been examined in several populations but the results have been inconsistent. The aim of this study was to evaluate the correlation of DQB1 alleles with TB patients and healthy controls in the same ethnic group in Poland. Method: The DQB1 alleles of 38 patients with TB and 58 healthy university staff volunteers were determined by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Alleles HLA-A*31 and HLA-B*55, with higher frequencies in the patients group, may also contribute to an impaired humoral response and thus be involved in susceptibility to leptospirosis, as they were associated with IgG subgroup deficiency (IgGSD) in a North American cohort [22]. Some HLA alleles outside the 8.1 haplotype with increased frequencies in the patient group have been associated with other infections, namely, HIV (HLA-B*55, HLA-B*58, and HLA-Cw*04 have a positive association with disease progression) [23], HBV (HLA-DRB1*13 appears to be protective) [24], HCV (HLA-Cw*04 is related to the persistence of the infection) [25], tuberculosis (HLA-DQB1*05 confers susceptibility) [26], dengue hemorrhagic fever (HLA-A*31 relates to susceptibility and HLA-DRB1*04 to protection) [27,28], and human papillomavirus (HPV; HLA-DRB1*04, HLA-DRB1*13, and HLA-DQB1*05 appear to provide some protection) [29,30]. The influence of HLA class I polymorphisms in the susceptibility to leptospirosis is probably related to alterations in the affinity of the HLA molecule binding site to the leptospiral antigens.…”
Section: Discussionmentioning
confidence: 97%
“…Alleles HLA-A*31 and HLA-B*55, with higher frequencies in the patients group, may also contribute to an impaired humoral response and thus be involved in susceptibility to leptospirosis, as they were associated with IgG subgroup deficiency (IgGSD) in a North American cohort [22]. Some HLA alleles outside the 8.1 haplotype with increased frequencies in the patient group have been associated with other infections, namely, HIV (HLA-B*55, HLA-B*58, and HLA-Cw*04 have a positive association with disease progression) [23], HBV (HLA-DRB1*13 appears to be protective) [24], HCV (HLA-Cw*04 is related to the persistence of the infection) [25], tuberculosis (HLA-DQB1*05 confers susceptibility) [26], dengue hemorrhagic fever (HLA-A*31 relates to susceptibility and HLA-DRB1*04 to protection) [27,28], and human papillomavirus (HPV; HLA-DRB1*04, HLA-DRB1*13, and HLA-DQB1*05 appear to provide some protection) [29,30]. The influence of HLA class I polymorphisms in the susceptibility to leptospirosis is probably related to alterations in the affinity of the HLA molecule binding site to the leptospiral antigens.…”
Section: Discussionmentioning
confidence: 97%
“…Poland [82] DQB1*05 *These are some of the representative population studies from various continents. Heterodimer DQA1*0501-DQB1*0201/02 Dutch [65] DQ2 Homozygotes, DQA1*05-DQB1*02/DQA1*0201-DQB1*02 heterozygotes France [66] HLA-DQ2 (DQA1*0501/DQB1*0201) and DR53 Italy [67] HLA-DQ2 Netherlands [68] HLA-DQ2.5/2.5 homozygotes, HLA-DQ2.5/2.2 heterozygotes Norway [69] HLA-DQ2 (DQA 1*0501, DQB 1*0201) Spain [70] HLA-DRB1*04 (DR4) *These are some of the representative population studies from various continents.…”
Section: Europementioning
confidence: 99%
“…Several studies have supported a weak to moderate association of HLA with TB; the implicated antigens include HLA-DR2, encoded by HLA-DR*15 and HLA-DR*16 alleles in Indians, Indonesians, and Poles [9 -13], -DR13 in Poles [14], -DR14 in Iranians [15], HLA-DQB1 in Cambodians and Poles [16,17], and HLA-DQw1 in Indonesians [10]. However, other studies have reported no such associations [18 -20].…”
Section: Introductionmentioning
confidence: 99%